Effect of ultrasonic power applied to micro-arc oxidation on the morphology, chemistry, wettability and electrical properties of calcium phosphate coatings on titanium - Komarova E. G. Ekaterina Gennadjevna; Akimova E. B. Elizaveta Borisovna; Kazantseva E. A. Ekaterina Aleksandrovna; Zharin A. I.; Sharkeev Yu. P. Yury Petrovich (2025, 2025)
Title screen